Feasibility Study of a Fan-Driven Device Generating Downforce for Road Cars - Maciej Szudarek; Adam Piechna; Janusz Piechna (Energies, 2022)
This paper, submitted to the special issue of Energies “Future of Road Vehicle Aerodynamics”, proposes and justifies the use of an old idea of generating downforce by actively drawing air from under the car body and exhausting it to the outside. Instead of traditional moving mechanical-curtain elements, a new method for sealing the clearance under the body with an air curtain is proposed. Basic information on the geometry and flow characteristics of such a solution suitable for use in automobiles is presented. The performance of such a fan-driven device generating downforce is studied over a wide range of driving speeds. The device allows for significantly improved vehicle acceleration, shorter braking distances, and extension of the range of safe cornering speeds. The paper shows the successive stages of development of the idea, from the 2D model to the 3D model, and an attempt to implement the device on a sports car. The distributions of pressure, velocity, pathlines and values of aerodynamic forces obtained at assumed fan compressions for different driving speeds are presented. The advantages and disadvantages of the analyzed device are discussed, and further optimization directions are outlined.